Proceedings of the 1999 Symposium on Interactive 3D Graphics 1999
DOI: 10.1145/300523.300537
|View full text |Cite
|
Sign up to set email alerts
|

Interactive ray tracing

Abstract: We examine a rendering system that interactively ray traces an image on a conventional multiprocessor. The implementation is "brute force" in that it explicitly traces rays through every screen pixel, yet pays careful attention to system resources for acceleration. The design of the system is described, along with issues related to material models, lighting and shadows, and frameless rendering. The system is demonstrated for several different types of input scenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 157 publications
(67 citation statements)
references
References 19 publications
(6 reference statements)
0
67
0
Order By: Relevance
“…Independently from hardware, ray tracing solutions have recently started to implement progressive rendering techniques [79]. Over the years many different methods emerged to follow this concept based on interactive path tracing [80] [81].…”
Section: Computationmentioning
confidence: 99%
“…Independently from hardware, ray tracing solutions have recently started to implement progressive rendering techniques [79]. Over the years many different methods emerged to follow this concept based on interactive path tracing [80] [81].…”
Section: Computationmentioning
confidence: 99%
“…While the first interactive ray tracer was proposed by Parker et al in (Parker et al, 1999) using a large shared memory supercomputer, interactive frame rates rendering using ray tracing still remains a non trivial task. Most of the time, an acceleration structure is built over the scene in order to improve ray tracing performances.…”
Section: Related Workmentioning
confidence: 99%
“…Our work stems from that of Parker et al [2], which demonstrated one of the first interactive ray tracing systems. By exploiting the capabilities of the SGI Origin series of shared memory supercomputers, they were able to achieve interactive frame rates using a brute force implementation of the ray tracing algorithm.…”
Section: Related Workmentioning
confidence: 99%